The importance of the electric sector: a national and regional input-output analysis - Takasago, Milene; Ferreira, Vinícius de Almeida Nery; Oliveira, João Maria de (Revista Economia Ensaios, 2024)
This paper analyzes the structural evolution of the electric sector in Brazil between 2010 and 2019 using the Input-Output framework. National results show that the industry has above average production multipliers that follow Brazilian economic performance and is considered a key sector – especially due to its supply –, having linkages with all other activities that exceed the economy’s average. Given its importance, the paper analyzes the regional gains and spillovers from larger investments in the sector, revealing that the Northeast is the region with the most significant impact on production, taxes, employment, and salaries.